2014
DOI: 10.1371/journal.pbio.1001881
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-2α Is an Essential Catabolic Regulator of Inflammatory Rheumatoid Arthritis

Abstract: Hypoxia-inducible factor-2α (HIF-2α) is sufficient to cause experimental rheumatoid arthritis and acts to regulate the functions of fibroblast-like cells from tissue surrounding joints, independent of HIF-1α.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(116 citation statements)
references
References 34 publications
3
112
0
1
Order By: Relevance
“…4G). Interestingly, we found that the expression of Il6, Cxcl2, Nos2, and Il1b mRNAs, which are produced in macrophages and fibroblasts (37)(38)(39)(40), was strongly upregulated in inflammatory joints from Il1r2 2/2 mice (Fig. 4H).…”
Section: Il1r2mentioning
confidence: 90%
“…4G). Interestingly, we found that the expression of Il6, Cxcl2, Nos2, and Il1b mRNAs, which are produced in macrophages and fibroblasts (37)(38)(39)(40), was strongly upregulated in inflammatory joints from Il1r2 2/2 mice (Fig. 4H).…”
Section: Il1r2mentioning
confidence: 90%
“…Despite the role of HIFs in the cellular adaptations, studies were concluded their deleterious inflammatory effects in tissue under normoxia/hypoxia that resulted in autoimmune disorders like rheumatoid arthritis, inflammatory bowel disease, multiple sclerosis, and psoriasis The loss of HIF‐1α blunted the inflammatory response in mouse models of cutaneous inflammation and arthritis . The pro‐inflammatory effect was found to be associated with the crosstalk between the NF‐kB signalling and also due to the excess production of nitric oxide .…”
Section: Hypoxia‐inducible Factors In Inflammationmentioning
confidence: 99%
“…5A). Because NF-κB previously had been shown to induce IL-1β expression in FLS and HIF-2α expression in chondrocytes (11,20,21), we further examined whether LOX-mediated activation of NF-κB is capable of inducing IL-1β and HIF-2α. Neither LOX nor HIF-2α induced IL-1β expression in chondrocytes (Fig.…”
Section: Cellular Lox Promotes Oa Pathogenesis By Modulating Chondrocytementioning
confidence: 99%